Determination of an Injection Sprayer's Technological Parameters - L. A. Marchenko; M. A. Safonov (Сельскохозяйственные машины и технологии, 2018)
Agricultural boom sprayers are equipped with injection sprayers of mainly foreign origin. The main parameters of the injection sprayers shown in the catalogs display the consumption characteristics in certain ranges without taking into account the design parameters. (Research purpose) Determination of the design and technological parameters of an injection sprayer for the introduction of pesticides. (Materials and methods) The injection sprayer belongs to the class of twophase liquidgas isothermal jet devices with the formation of an airgas mixture at the outlet. It has been established that the design model of the working process of an injection sprayer is based both on the laws of the conservation of mass, energy, momentum, as well as theoretical relationships in the form of equations describing twophase jet devices, and empirical relationships characterizing flow parameters, geometric transverse and longitudinal dimensions of the spray channels. (Results and discussion) The following analytical relationships have been obtained: the relative pressure difference generated by an injection sprayer and the volume injection coefficient for different surface area ratios of the working nozzle to the flow section of the sprayer; the ratio between the crosssectional area of the mixing chamber to the area of the working nozzle outlet and the injection ratio; relative pressure difference and the injection ratio; the ratio between the crosssectional area of the mixing chamber and the working nozzle and the relative pressure difference. The authors have determined a set of dimensionless pressure characteristics of the injection sprayer for different ratios between the crosssectional areas of the working nozzle and the mixing chamber. It has been established that the ratio between the cross sections of the mixing chamber area and the working nozzle area increases as the injection ratio increases. It has been shown that for each injection coefficient, there is an achievable relative pressure difference in the injection sprayer. (Conclusions) The authors have proposed the design equations that determine the characteristics of an injection sprayer and its main design parameters – the diameters of nozzle and mixing chambers. They have calculated the main dimensions of the sprayer for aerial topdressing by introducing working solutions of pesticides.